R2Cross: A Web‐Based Decision Support Tool for Instream Flows. (9th July 2021) - Oikonomou, Panagiotis D.; Sidhu, Rumpal; Wible, Tyler; Morrison, Ryan R.
Abstract: The determination of instream flows for preserving or improving aquatic ecosystems' health often includes challenges caused by varied hydraulic conditions, ecological criteria, and socioeconomic considerations. Despite the abundance of available methodologies, there are few available desktop or online applications enabling rapid assessment of instream flows that incorporate pertinent geospatial information for the region. We present R2Cross, a user‐friendly, online, instream flow rate calculation tool that was developed for aiding water allocation decisions in the state of Colorado. The R2Cross tool is the only existing online decision support tool based on a hydraulic rating method. It estimates hydraulic conditions at different water stages in a stream reach and compares them to habitat criteria to determine biological instream flow recommendations. Cloud‐based Geographic Information System features and additional tools are incorporated that augment information and aid in evaluating ecological needs. The development of the R2Cross tool enables an open‐access interface for management authorities and stakeholders to evaluate ecological needs at stream reaches. It automates the reporting process and could assist in making water management decisions about environmental protection. Although the R2Cross tool was developed for the state of Colorado, it is generalizable to other stream systems assuming similar habitat criteria. Abstract : Research Impact Statement : R2Cross is an intuitive and robust web‐accessible tool for assessing instream flow criteria. It fills a gap in publicly available online tools as it is uniquely based on a hydraulic rating method.